In vivo and in vitro Digestibility of an Extruded Complete Dog Food Containing Black Soldier Fly (Hermetia illucens) Larvae Meal as Protein Source - Penazzi, Livio; Schiavone, Achille; Russo, Natalia; Nery, Joana; Valle, Emanuela; Madrid, Josefa; Martinez, Silvia; Hernandez, Fuensanta; Pagani, Elena; Ala, Ugo; Prola, Liviana (Frontiers in Veterinary Science, 2021)
Growing attention is being directed toward insects as a novel and sustainable source of protein for pet food. The aim of the study was to evaluate nutrient digestibility of a diet containing black soldier fly larvae as its main protein source. Moreover, purpose of the study was to compare the traditional in vivo total collection method with in vivo marker method and in vitro digestibility method. Two isonitrogenous and isoenergetic dry diets containing either venison meal (CTRL diet) or black soldier fly larvae meal (BSF diet) as their primary sources of proteins were fed to six adult dogs, according to a Latin square design. The digestibility of nutrients was determined using both in vivo (‘total collection’ and ‘internal marker’ approaches) and in vitro methods. The two diets showed similar nutrient digestibility values for: dry matter, organic matter, ether extract, ash, and phosphorus. However, a statistical trend (p = 0.066) was observed indicating greater protein digestibility in the BSF diet compared with the CTRL diet. Calcium digestibility was higher in the BSF diet compared with the CTRL diet (p = 0.018). On the contrary, fiber digestibility was lower in the insect-based diet compared with the venison diet (p < 0.001). There was no difference between total collection and internal marker methods in the assessment of in vivo digestibility for any of the nutrients considered. The in vitro digestibility values for dry matter, organic matter, and crude protein, as well as the estimated in vivo digestibility of organic matter and crude protein by the means of the predictive equation, were aligned with the in vivo results, although in vitro estimations were consistently higher compared with those obtained by in vivo analysis. Digestibility analysis of a dog food containing insect meal as the sole source of protein (36.5% inclusion) showed promising results in terms of it presenting similar values as a meat-based diet, indicating its suitability as a sustainable protein source for pet food. Moreover, the study showed that both the in vivo marker method and the in vitro method could be possible alternatives to the traditional total collection method in digestibility trials.